Optimization of Predictive Performance for the Therapeutic Response Using Iodine Scan-Corrected Serum Thyroglobulin in Patients with Differentiated Thyroid Carcinoma - Yoo, Su Woong (Cancers (Basel), 2020)
We investigated whether the performance of serum thyroglobulin (Tg) for response prediction could be improved based on the iodine uptake pattern on the post-therapeutic I-131 whole body scan (RxWBS) and the degree of thyroid tissue damage with radioactive iodine (RAI) therapy. A total of 319 patients with differentiated thyroid carcinoma who underwent total thyroidectomy and RAI therapy were included. Based on the presence/absence of focal uptake at the anterior midline of the neck above the thyroidectomy bed on RxWBS, patients were classified into positive and negative uptake groups. Serum Tg was measured immediately before (D0Tg) and 7 days after RAI therapy (D7Tg). Patients were further categorized into favorable and unfavorable Tg groups based on the prediction of excellent response (ER) using scan-corrected Tg developed through the stepwise combination of D0Tg with ratio Tg (D7Tg/D0Tg). We investigated whether the predictive performance for ER improved with the application of scan-corrected Tg compared to the single Tg cutoff. The combined approach using scan-corrected Tg showed better predictive performance for ER than the single cutoff of D0Tg alone (p < 0.001). Therefore, scan-corrected Tg can be a promising biomarker to predict the therapeutic responses after RAI therapy.